COMPARISON OF 0.7 MG AND 1 MG PROTAMINES ON ACTIVATED CLOTTING TIME AND BLEEDING IN OFF-PUMP CORONARY ARTERY BYPASS PATIENTS: A MULTICENTER STUDY - Andika Ahadyat Lukman Wiriaatmaja; Reza Widianto Sudjud; Budiana Rismawan (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
Background: Optimal anticoagulation management is crucial for graft patency and minimizing postoperative complications in off-pump coronary artery bypass grafting (OPCAB), a widely performed surgical procedure for coronary artery disease. The role of protamine in neutralizing heparin and its impact on activated clotting time (ACT) and postoperative bleeding remain unclear. This study compared the effects of two protamine doses (0.7 mg and 1 mg per 1 mg of heparin) on ACT and bleeding outcomes in patients who underwent OPCAB. Methods: This multicenter, single-blind, randomized controlled trial was conducted from February to April 2025 and included 50 patients undergoing OPCAB at Dr. Hasan Sadikin General Hospital and Santosa Hospital Central. Patients were randomized into two groups: Group 1 received 0.7 mg of protamine per 1 mg of heparin, and Group 2 received 1 mg of protamine per 1 mg of heparin. The primary outcomes were post-protamine ACT levels and postoperative bleeding at 1, 4, and 12 h. The secondary outcomes included the need for colloid and crystalloid fluid administration. Results: The results showed No significant difference was observed in the ACT between the two groups after protamine administration (p = 0.541). However, postoperative bleeding was significantly lower in the 0.7 mg group than in the 1 mg group at all postoperative time points (p < 0.05). The 1 mg protamine group required significantly more colloid infusion during the procedure (p = 0.001), suggesting greater hemodynamic instability associated with higher protamine doses. Conclusions: A protamine dose of 0.7 mg per 1 mg of heparin was associated with less postoperative bleeding than the standard 1 mg dose, without significant differences in ACT. These findings suggest that lower doses of protamine may be preferable in OPCAB to reduce bleeding risk while maintaining effective heparin neutralization. Further studies are needed to refine the protamine dosing protocols for cardiac surgery.